Active locust bean gum-guar gum aerogels containing Heracleum persicum essential oil and chitosan nanoparticles to extend the shelf-life of peeled shrimps - Nassim Shavisi; Yasser Shahbazi (Applied Food Research)
This study aimed to design locust bean gum-guar gum (LBG-GG) aerogels containing Heracleum persicum essential oil (HPE, 0.5 %) and chitosan nanoparticles (CNP, 1 %) to increase the shelf-life of freshly peeled shrimps in the time of 12 days of storage under chilled conditions. Butanoic acid, 2-methyl hexyl ester (36.18 %), acetic acid, octyl ester (22.94 %), and butanoic acid, octyl ester (5.15 %) were the major chemical constituents of Heracleum persicum fruit essential oil. The water solubility, moisture content, and water vapor sorption capacity of LBG-GG + HPE 0.5 %, LBG-GG + CNP 1 %, and LBG-GG + HPE 0.5 % + CNP 1 % aerogels were significantly lower than those of the straight LBG-GG aerogel (p < 0.05), by 7.19 %-16.90 %, 0.10 %-0.13 %, and 1.80 %-5.12 %, respectively. Peeled shrimps packaged with the LBG-GG + HPE 0.5 % + CNP 1 % aerogel had significantly lower total viable count, psychrotrophic bacterial count, Enterobacteriaceae, H2S-producing bacteria, total volatile basic nitrogen, and peroxide value than the untreated samples after 12 days of storage under refrigerated conditions (p < 0.05), recorded by 5.80 log CFU/g, 5.12 log CFU/g, 4.03 log CFU/g, 3.76 log CFU/g, 15.77 mg N/100 g, and 0.56 meq peroxide/kg, respectively. Our findings suggest that LBG-GG + HPE 0.5 % + CNP 1 % aerogel may be a novel active packaging material with antimicrobial and antioxidant properties for shrimp preservation.